2022
DOI: 10.1101/2022.02.04.479105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speech understanding oppositely affects acoustic and linguistic neural tracking in a speech rate manipulation paradigm

Abstract: When listening to continuous speech, the human brain can track features of the presented speech signal. It has been shown that neural tracking of acoustic features is a prerequisite for speech understanding and can predict speech understanding in controlled circumstances. However, the brain also tracks linguistic features of speech, which may be more directly related to speech understanding. We investigated acoustic and linguistic speech processing as a function of varying speech understanding by manipulating… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…However, as EEG follows a 1/f-characteristics, a broader frequency range would follow similar patterns as the delta band. In line with our results, Kosem et al (2022) and Verschueren et al (2022) also did not see a link between acoustic tracking and speech comprehension. Altogether, this suggests that acoustic tracking is a necessity rather than a sufficient condition for speech comprehension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, as EEG follows a 1/f-characteristics, a broader frequency range would follow similar patterns as the delta band. In line with our results, Kosem et al (2022) and Verschueren et al (2022) also did not see a link between acoustic tracking and speech comprehension. Altogether, this suggests that acoustic tracking is a necessity rather than a sufficient condition for speech comprehension.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that there is a link between acoustic tracking and speech comprehension. However, recent studies by Kosem et al (2022) and Verschueren et al (2022) showed that this link between acoustic tracking and comprehension is not always observed. More specifically, by manipulating speech comprehension by either using noise-vocoded speech or changing the speech rate, they observed that as the speech became comprehensible, acoustic tracking did not increase.…”
Section: Introductionmentioning
confidence: 96%
“…If this is so, then language comprehension can be seen as a neural filter over sensory and perceptual input in service of the transformation of that input into linguistic structures. A similar effect was also shown for increasing speech rate; tracking performance of linguistic features decreased and tracking performance of acoustic features increased with decreasing intelligibility (Verschueren et al, 2022).…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, however, in both experiments performance decreased later than previously observed, that is, beyond rates of 9 syllables/s(56,80). However, in line with our findings, several other studies, also observed shallower decreases in speech comprehension, with relatively high comprehension at higher syllable rates (~12 syllables/s)(3,56,81,82). We consider several possible explanations for these discrepancies.…”
Section: Discussionsupporting
confidence: 93%